Normothermic Crystalloid Polarizing Cardioplegia Improves Systolic and Diastolic Function in a Porcine Model of Cardiopulmonary Bypass - David Santer; Stefan Heber; Anne-Margarethe Kramer; Judith Radloff; Katharina Heissl; Attila Kiss; David J. Chambers; Seth Hallström; Bruno K. Podesser (Biomedicines)
Background/Objectives: Previously, we showed that blood-based polarizing cardioplegia exerted beneficial cardioprotection during hypothermic ischemia; however, these positive effects of blood-based polarizing cardioplegia were reduced during normothermic ischemia compared to blood-based hyperkalemic (depolarizing) cardioplegia. This study compares crystalloid polarizing cardioplegia to crystalloid depolarizing cardioplegia in a normothermic porcine model of cardiopulmonary bypass; Methods: Twelve pigs were randomized to receive either normothermic polarizing (n = 7) or depolarizing (n = 5) crystalloid cardioplegia. After the initiation of cardiopulmonary bypass, normothermic arrest (34 °C, 60 min) was followed by 60 min of on-pump and 90 min of off-pump reperfusion. Myocardial injury (arterial CK-MB), hemodynamic function, and the energy status of the hearts were measured; Results: The arterial release of CK-MB was comparable between groups (p = 0.78) during reperfusion. During 150 min of reperfusion, systolic left ventricular pressure (p = 0.01) and coronary flow (p = 0.009) were increased, and wedge pressure (p = 0.04) was decreased in the polarized group. Further hemodynamic parameters (cardiac output, stroke volume) and high-energy phosphate levels were similar between groups. The requirement for noradrenaline administration during reperfusion was significantly higher (p = 0.013) in the polarized group; Conclusions: Under normothermic conditions and despite a similar increase in levels of cardiac CK-MB, crystalloid polarizing cardioplegia protected systolic and diastolic cardiac function after 60 min of cardiac arrest. These results suggest beneficial effects for polarizing cardioplegia; clinical studies are required to confirm these effects.